Workload Analysis to Determine the Optimal Number of Human Resources at Sariraya Co., Ltd - Faryaputra, Fauzan Nafisa; Sudiana, Kiki (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Sariraya Co., Ltd is a pioneer Indonesian halal food chain based in Aichi, Japan. Sariraya specializes in halal food chains in Japan with several business units such as tempeh factories, restaurants, and halal marts. As a company with many units, workload is one of the main factors in work efficiency that influences work productivity. This research aims to determine the workload conditions. Analysis is carried out to find the optimal amount by considering the volume of work, the number of workers, and the time needed to complete a job. Job analysis is also conducted in the form of structure organization and job description of Sariraya Co., Ltd Warehouse Unit. This research uses descriptive techniques through a qualitative approach with all warehouse employees as the main source of data research. The Full-Time Equivalent Method is used as the data analysis technique. Data was collected using questionnaires and structured interviews with permanent employees of the Sariraya Warehouse Co., Ltd. unit. Based on the results of the Full-Time Equivalent calculation, it was found that there were employees who had an excessive workload (overload) of 2 people, a shortage (underload) of 1 person and there was no optimal employee workload (inload). Apart from that, it was also found that there was a backlog of work for 1 person with an FTE score > 2.2. The final score for the total workload received by warehouse employees was 6.2691046. So, management should add 2 more people so that the existing workload can be optimal. Hence, this research can be used as a consideration for management in determining the appropriate job descriptions and number of employees so that employees receive optimal workloads to achieve optimal employee performance.